Fibrosis quantification in Hypertensive Heart Disease with LVH and Non-LVH: Findings from T1 mapping and Contrast-free Cardiac Diffusion-weighted imaging - Wu, Lian-Ming; Wu, Rui; Ou, Yang-Rongzheng; Chen, Bing-Hua; Yao, Qiu-Ying; Lu, Qing; Hu, Jiani; Jiang, Meng; An, Dong-Aolei; Xu, Jian-Rong (Scientific reports, 2017)
This study assessed the extent of fibrosis and the relationship between the ADC value and systolic strain in hypertensive patients with left ventricular hypertrophy (HTN LVH) and hypertensive patients without LVH (HTN non-LVH) using cardiac diffusion-weighted imaging and T1 mapping. T1 mapping was performed in 13 HTN LVH (mean age, 56.23 ± 3.30 years), 17 HTN non-LVH (mean age, 56.41 ± 2.78 years), and 12 normal control subjects (mean age, 55.67 ± 3.08 years) with 3.0 T MRI using cardiac diffusion-weighted imaging and T1 mapping. HTN LVH subjects had higher native T1 (1233.12 ± 79.01) compared with controls (1133.88 ± 27.40) (p < 0.05). HTN LVH subjects had higher ECV (0.28 ± 0.03) compared with HTN non-LVH subjects (0.26 ± 0.02) or controls (0.24 ± 0.03) (p < 0.05). HTN LVH subjects had higher ADC (2.23 ± 0.34) compared with HTN non-LVH subjects (1.88 ± 0.27) or controls (1.61 ± 0.38), (p < 0.05). Positive associations were noted between LVMI and ADC (Spearman = 0.450, p < 0.05) and between LVMI and ECV (Spearman = 0.181, p < 0.05). ADC was also related to an increase in ECV (R 2 = 0.210). Increased levels of ADC were associated with reduced peak systolic and early diastolic circumferential strain rates across all subjects. Contrast-free DW-CMR is an alternative sequence to ECV for the evaluation of fibrosis extent in HTN LVH and HTN non-LVH, while native T1 has limited value.